Comparative Study of Cyberchondriasis and OCD Among Covid and NonCovid Respondents - Khudija Zahid; Dr. Shazia Gul; Zartasha Munawar (International Journal of Business and Economic Affairs, 2024)
The current study examined the relationship between cyberchondriasis and obsessive-compulsive disorder in 300 covid and non-covid respondents from various universities in the Hazara region. These students were chosen using purposive and snowball sampling methods. In the current study, the Yale Brown OCD Scale YBOCS and the 12-item short version of the Cyberchondria Severity Scale were used. Reliability analysis, Correlation, t-test were used in order to test relationship between variables. Findings revealed that covid experience is more commonly linkedto cyberchondriasis and obsessive-compulsive symptoms than non-covid experience. Men are more prone to develop cyberchondriasis than women, and it has also been demonstrated that women have more OCD symptoms than men do.